(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article examines the effectiveness of interactive learning strategies in developing students’ speaking skills in English language classrooms. In today’s communicative-oriented education system, speaking competence is considered a key indicator of language proficiency. Traditional teaching methods often fail to engage students in active communication, while interactive strategies such as role-play, debates, brainstorming, and collaborative tasks create authentic opportunities for oral practice. The study highlights how these strategies increase student motivation, enhance critical thinking, and foster a learner-centered environment. Findings suggest that integrating interactive learning into English language teaching not only improves fluency and accuracy but also builds students’ confidence in real-life communication.